Aplikasi Sistem Penomoran Surat Otomatis Berbasis Website Di PERUMDA Tirtanadi Medan - Purba, Sentia Ovania; Muhathir, Muhathir (Jurnal Ilmiah Teknik Informatika & Elektro (JITEK), 2025)
The management of official letters that are still carried out manually at PERUMDA Tirtanadi Medan causes various problems, such as difficulties in obtaining letter numbers, waste of agenda books, delays in completing letters, and the potential for numbering errors. This research aims to design and develop a website-based automatic mail numbering system application to improve efficiency and accuracy in managing incoming and outgoing mail. The research methods used include requirements analysis, system design using Data Flow Diagram (DFD) and Entity Relationship Diagram (ERD), implementation with PHP, MySQL, and Bootstrap 5 technology, and system testing using the black-box testing method. The results of the study show that the system developed can speed up the mail management process, reduce errors in numbering, and improve operational efficiency in each division. With this system, employees can access mail data more flexibly and structured through a web-based platform. The implementation of this system is expected to be a solution in overcoming mail management problems at PERUMDA Tirtanadi Medan and supporting the improvement of more modern and professional administrative performance.